Reflexões sobre o ensino de bioética e cuidados paliativos nas escolas médicas do Estado de Minas Gerais - Jose Ricardo de Oliveira (2014)
The teaching of palliative care in the Medical School courses in the state of Minas Gerais is paramount to understand the relation between medicine-physician-health care interdisciplinary team regarding the finity of human life. The main theme of this work is the analysis of Minas Gerais Medical Schools curriculum with the objective of verifying how the teaching of palliative care is inserted in these schools graduation courses. An exploratory case study of qualitative nature used three operational tools: survey, interview and electronic document, in four stages. In the first stage 28 schools were consulted in order to verify how palliative care and bioethics were taught. In the second stage, a fieldwork was conducted with structured interviews being applied to students in two medical schools and also the deepening of the study. In the second stage a fieldwork was conducted with structured interviews being applied to students in two medical schools. In the third stage, the data acquired in previous stages were compiled and compared to national and international literature on academic formation in bioethics and palliative care. In the fourth stage, students in the last year of the medical school were interviewed. This last stage allowed a critical and transversal discussion of the academic formation in said field. The results showed that bioethics knowledge focusing on palliative care and also on the formation of physicians who work with this health fields emergent needs was not well covered in the medical schools of Minas Gerais. Also there was not a correlation between ethics and bioethics teaching and the teaching of palliative care. The articulation between the teaching of bioethics and palliative care is underinvestigated in the health field. Considering the lack of concern over the teaching of bioethics with focus on palliative care, we propose a reflection and a programmatic action in the formation of teachers and also the insertion of the transversal and specific curricular teaching of bioethics and palliative care in the graduation curriculum of the medical schools of Minas Gerais.